Improved anti-diabetic activity of glibenclamide using oral self nano emulsifying powder. (February 2015) - Bari, Abdul; Chella, Naveen; Sanka, Krishna; Shastri, Nalini R.; Diwan, Prakash V.
Abstract The objective of the present study was to improve solubility, dissolution rate and therapeutic efficacy of a BCS Class II drug, glibenclamide by using oral self nano emulsifying powder. The powder was prepared by adsorbing the mixture of oil, surfactant and co-surfactant onto a carrier with large surface area; Aerosil 200. The ratios of oil and Smix (surfactant/co-surfactant mixture) required to produce an emulsion was optimized based on percentage transmittance studies and particle size determinations. The optimized formulation was subjected to in vitro dissolution study and in vivo therapeutic efficacy in rabbits by monitoring blood glucose levels. Scanning electron microscopy, differential scanning calorimetry and X-ray powder diffraction studies revealed that the drug was present in amorphous form in the final formulation. The in vivo study in rabbits indicated the improved therapeutic efficacy of glibenclamide in self-nanoemulsifying powder compared to plain drug.